1988
DOI: 10.2220/biomedres.9.181
|View full text |Cite
|
Sign up to set email alerts
|

<b>DIFFERENCES IN PROLIFERATION PROPERTIES AMONG SUBLINES OF RAT 3Y1 FIBROBLASTS TRANSFORMED BY VARIOUS AGENTS <i>IN </i></b><b><i>VITRO </i></b>

Abstract: Alterations in cellular characteristics associated with transformation were compared among various agents, including simian virus 40, mouse polyoma virus, adenovirus type 12, the ElA region of adenovirus type 12, Rous sarcoma virus, v-Hras oncogene, and N-methyl-N'-nitro-N-nitrosoguanidine. To avoid the difficulty in interpretation due to differences in the original cellular characteristics, all transformed lines (three to four independent lines for each agent) were derived from the same parental line, i.e. ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…[4][5][6][7] The HR-3Y1-2 cell line established by Kimura et al was derived from 3Y1 rat fibroblasts transformed with the v-H-ras oncogene. 8) Anchorageindependent proliferation and changed cellular morphology are known features of 3Y1 cells transformed with v-H-ras, 9) and our preliminary study has shown that HR-3Y1-2 cells were capable of proliferating faster than the parent 3Y1cell line. Therefore, these cell lines are useful for evaluating the effects of various treatments on the malignant characteristics derived from Ras activation.…”
mentioning
confidence: 88%
“…[4][5][6][7] The HR-3Y1-2 cell line established by Kimura et al was derived from 3Y1 rat fibroblasts transformed with the v-H-ras oncogene. 8) Anchorageindependent proliferation and changed cellular morphology are known features of 3Y1 cells transformed with v-H-ras, 9) and our preliminary study has shown that HR-3Y1-2 cells were capable of proliferating faster than the parent 3Y1cell line. Therefore, these cell lines are useful for evaluating the effects of various treatments on the malignant characteristics derived from Ras activation.…”
mentioning
confidence: 88%
“…SR-3Y1 is a 3Y1 cell line transformed by v-Src of Rous sarcoma virus (Zaitsu et al, 1988). Abl-negative ®broblasts are kindly given from Dr BJ Mayer.…”
Section: Cellsmentioning
confidence: 99%
“…ts2 and ts3 are SV3Y1tsD123 derivatives overexpressing the mutated D123 protein of 3Y1tsD123, obtained by transfecting SV-3Y1tsD123 with expression plasmid carrying the mutated D123 cDNA and the hygromycin B marker (Okuda et al, 1999). SV-3Y1-C66 (referred to as SV-3Y1) is an SV40-transformed derivative of 3Y1 (Zaitsu et al, 1988).…”
Section: Cell Culturementioning
confidence: 99%